Incidence of Orbital Trauma in Gunshot Injuries during July Revolution of 2024 in Bangladesh - Ahmed, Monir Uddin; Kadir, Syeed Mehbub Ul; Hossain, Mahbub; Ali, Md Ishaque; Chowdhury, Md Nazrul Islam (Community Based Medical Journal, 2026)
A significant civilian casualties due to gunshot wounds with orbital injuries, being a particularly devastating type of trauma, were incurred during the July Revolution of 2024 in Bangladesh. Those injuries resulted in complex ophthalmic and craniofacial damage that required specialised care. This study aims to describe the pattern of injuries, management procedures, and visual outcomes of orbital gunshot injuries treated in the National Institute of Ophthalmology & Hospital (NIOH), Dhaka, Bangladesh, a specialized, tertiary-level eye care hospital in the country. This cross-sectional study was conducted between July and December of 2024. A total of 612 patients were included in this study among total 1002 firearm trauma presentations. Detailed information about the patients' surgical interventions, visual outcomes, and imaging findings were documented. Among 1002 gunshot injury patients, 612(61.1%) had orbital involvement, predominantly unilateral (93.6%). Radiological evaluation revealed the presence of metallic foreign bodies (68.5%) and fractures (52.3%). About 82.4% of cases with orbital injuries need ocular and adnexal surgery. Approximately 64% of the procedures involved vitreoretinal surgery. Postoperatively, 73% of patients experienced some improvement in vision; however, those with bilateral injuries showed poorer outcomes, with 51.5% experiencing further vision loss. These findings highlight the severe ocular morbidity from conflict-related orbital trauma. Conclusion: Vision loss is the most frequent morbidity from orbitofacial injuries caused by gunshots. Bilateral cases tend to exhibit the most severe outcome. These findings emphasise the essential need for updated trauma strategies, protective gear, and improved eye care in conflict zones to preserve vision and reduce disability. CBMJ 2026 January: vol. 15 no. 01 P:67-73